2016
DOI: 10.1002/cpmo.12
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Phenotyping of the Adult Mouse Brain

Abstract: This article describes a series of standard operating procedures for morphological phenotyping of the mouse brain using basic histology. Many histological studies of the mouse brain use qualitative approaches based on what the human eye can detect. Consequently, some phenotypic information may be missed. Here we describe a quantitative approach for the assessment of brain morphology that is simple and robust. A total of 78 measurements are made throughout the brain at specific and well-defined regions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…We have previously shown that our quantitative and ultra‐standardized approach allowed us to detect many more features and more subtle phenotypes than previously published data (Mikhaleva et al. ).…”
Section: Methodsmentioning
confidence: 74%
“…We have previously shown that our quantitative and ultra‐standardized approach allowed us to detect many more features and more subtle phenotypes than previously published data (Mikhaleva et al. ).…”
Section: Methodsmentioning
confidence: 74%
“…34 Mouse brain samples were perfused and post fixed in 4% PFA for 48 hr. Sixty-three brain parameters (area and length measurements) were measured blind to the genotype across two coronal sections (Bregma 0.98 mm and À1.34 mm) as described 35 and data were analyzed using a Student two-tailed equal variance test. Using in-house ImageJ plugins, we quantified a series of cellular parameters including cell count, cell density, total and average cell area, and ratio of the parameter area over the cell area, in 15 regions combining white and gray matter structures (cingulate cortex, genu and soma of the corpus callosum, caudate putamen, anterior commissure, primary motor cortex, secondary somatosensory cortex, retrosplenial granular cortex, dorsal hippocampal commissure, amygdaloid nucleus, mammillothalamic tract, piriform cortex, internal capsule, fimbria of the hippocampus, habenula, and hypothalamus).…”
Section: Mouse Studiesmentioning
confidence: 99%
“…Neurological dysfunctions were also noted with an increased or absent threshold for auditory brainstem response (signs of hearing impairment) and diminished grip strength. As Aff3 is expressed in progenitor neurons 45 and required for neuronal migration in the cerebral cortex 46 , we further assessed the consequences of Aff3 disruption on brain development by measuring a standardized set of 78 parameters across 22 brain regions 34 . Compared with wild type males, homozygous Aff3 −/− , but not heterozygous Aff3 +/- males, exhibited significantly enlarged lateral ventricles ( p = 1.24 × 10 −04 ) and decreased corpus callosum size ( p = 3.02 × 10 −06 ; Figure 4 ), similar to the phenotypes observed in proband 2, 3 and 6 and in the previously reported deletion proband ( Table S1 , Figure S1 ) 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Laf4 ) gene 33 . Seventy-eight brain parameters were measured across three coronal sections as described 34 and data were analyzed using a mixed model and comparing to more than 100 wild-type males using a false discovery rate of 1%. Other metabolic and anatomical phenotypes were assessed by the Welcome Trust Sanger Institute through phenotyping of 6 to 13 homozygous and 7 to 14 heterozygous mice and are available on the International Mouse Phenotyping Consortium website.…”
Section: Methodsmentioning
confidence: 99%